Hybrid optimization shunt active power filter based on radar power system. (March 2023) - Wang, Yuetong; Li, Congcong; Li, Siqi; Wang, Dalian; Cheng, Tingli; Chen, Zhiwei; Zhang, Yingying
The problem of load nonlinearity is exposed as more and more load types are introduced into the radar power system. The nonlinear load is easy to produce large harmonic current, but at the same time it seriously threatens the normal and safe operation of other system equipment. How to design shunt active power filter (APF) to eliminate the harmonic effect of load and achieve stability as well reliability is a difficult problem for radar power system working at 115 V 400 Hz. This paper designs a hybrid optimization shunt active power filter, which can quickly detect and compensate harmonics, mainly includes fast harmonic detection module, space vector modulation module, composite control module and inverter module. Furthermore, the modeling and simulation of the hybrid optimization shunt APF are completed in MATLAB/Simulink software, and the parameters of radar power system are also redesigned. The simulation results suggest that, under heavy load conditions, the total harmonic distortion (THD) of the radar power side current is below 4.96%, and the short-period meaning filter only needs 0.0035 s to enter a new steady state in the face of load mutation. The APF designed in this paper can effectively suppress the harmonics in the radar power system, and greatly improve the dynamic performance while ensuring the steady-state performance of the system.